2020
DOI: 10.1159/000509629
|View full text |Cite
|
Sign up to set email alerts
|

Acute Bilateral Uveitis, Hypotony, and Cataracts Associated with Ipilimumab and Nivolumab Therapy: Optical Coherence Tomography Angiography Findings

Abstract: Immune checkpoint inhibitors are increasingly being used for the treatment of several malignancies. In rare cases, patients develop disabling ophthalmic side effects such as dry eyes, episcleritis, keratitis, uveitis, inflammatory orbitopathy, myasthenia gravis, macular edema, and serous retinal detachment. We present a case of acute bilateral anterior uveitis, prolonged hypotony, and cataracts following the use of dual therapy ipilimumab and nivolumab. Physicians should be aware of these immune-mediated ocula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Previous reports have shown that immune checkpoint inhibitors occasionally cause uveitis and hypotony. 8 , 9 , 10 It is thought that hypotony is caused by uveitis, trauma, medications, and ocular ischemia. 11 Our patient exhibited ipilimumab-related uveitis in both eyes, which probably led to hypotony.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have shown that immune checkpoint inhibitors occasionally cause uveitis and hypotony. 8 , 9 , 10 It is thought that hypotony is caused by uveitis, trauma, medications, and ocular ischemia. 11 Our patient exhibited ipilimumab-related uveitis in both eyes, which probably led to hypotony.…”
Section: Discussionmentioning
confidence: 99%
“…Most anterior uveitis were treated with topical treatment alone, with a positive outcome [ 16 , 19 , 22 , 25 , 26 , 27 , 38 , 41 , 44 , 45 , 48 , 52 , 59 , 63 , 102 ]. In the literature, uveitis recurrences have mainly been noted when patients resumed ICPI [ 17 , 61 ] sometimes with a different SUN anatomical classification.…”
Section: Discussionmentioning
confidence: 99%
“…Immunotherapies in the form of immune checkpoint inhibitors (ICIs) have been developed to treat many malignancies, including melanoma, and squamous cell carcinoma, amongst others [ 1 ]. Clinical trials have shown ICIs are efficacious, but patients report immune-related adverse effects (irAEs); at around 10-15% higher rate than patients receiving classic chemotherapy drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical trials have shown ICIs are efficacious, but patients report immune-related adverse effects (irAEs); at around 10-15% higher rate than patients receiving classic chemotherapy drugs. irAEs are mainly in the dermatological, gastrointestinal, hepatic, and endocrine systems [ 1 ]. However, 1% of patients may also manifest in the visual system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation